Environment and economy - Cato, Molly Scott (Routledge introductions to environment series, 2011)
As environmental issues move to the centre of the political debate, more attention is being focused on the role our economy has played in creating the ecological crisis, and what a sustainable economy might look like. In spite of the success of the environmental movement in drawing attention to the crisis facing us, there has been comparatively little attention focused on the way the operation of the global economy contributes to this crisis. Environment and Economy provides a stimulating introductory insight into the history of thinking that has linked the economy and the environment. It begins by introducing readers to the pioneers of this field, such as Fritz Schumacher and Paul Ehrlich, who first drew attention to the disastrous consequences for our environment of our ever-expanding economy. Part II of the book describes the main academic responses to the need to resolve the tension between economy and environment: environmental economics, ecological economics, green economics, and anti-capitalist economics. Part III is structured around key themes including an introduction to economic instruments such as taxes and regulation; pollution and resource depletion; growth; globalization vs. localization; and climate change. Each key issue is approached from a range of different perspectives, and working policies are presented in detail. -- Back cover.